Responses of Carbon Dynamics to Nitrogen Deposition in Typical Freshwater Wetland of Sanjiang Plain - Yang Wang; Jingshuang Liu; Longxue He; Jingxin Dou; Hongmei Zhao (Journal of Chemistry)
The effects of nitrogen deposition (N-deposition) on the carbon dynamics in typical Calamagrostis angustifolia wetland of Sanjiang Plain were studied by a pot-culture experiment during two continuous plant growing seasons. Elevated atmospheric N-deposition caused significant increases in the aboveground net primary production and root biomass; moreover, a preferential partition of carbon to root was also observed. Different soil carbon fractions gained due to elevated N-deposition and their response intensities followed the sequence of labile carbon > dissolved organic carbon > microbial biomass carbon, and the interaction between N-deposition and flooded condition facilitated the release of different carbon fractions. Positive correlations were found between CO2 and CH4 fluxes and liable carbon contents with N-deposition, and flooded condition also tended to facilitate CH4 fluxes and to inhibit the CO2 fluxes with N-deposition. The increases in soil carbon fractions occurring in the nitrogen treatments were significantly correlated with increases in root, aboveground parts, total biomass, and their carbon uptake. Our results suggested that N-deposition could enhance the contents of active carbon fractions in soil system and carbon accumulation in plant of the freshwater wetlands.